The Importance of Cross-Cultural Understanding in Foreign Language Teaching in The Asian Context - Ratnasari, Dian (citeus, 2018)
Foreign language learning is not only about grammar or vocabulary but also life skill to be able to communicate. Furthermore, mastering culture along with learning language is essential. Language learners must have knowledge of cultural understanding because every language reflects many kinds of cultures. The same thing can happen between Indonesian and German. If the communication is not good, it could lead to something negative, especially when the communications are related to business cooperation as well as other important partnerships. So, in foreign language learning, teachers must teach the cultures of both the native and foreign language too, so that learners can understand differences between German and Indonesian culture. This research is a kind of literature review research. The literatures were based on the result of previous studies on cultural differences in verbal communication between German and Indonesian culture. It is also supported by observing and studying reference system to generate appropriate learning strategies. The study reveals that there are various strategies that can be implemented to enable students to understand cultural differences. There is some cultural knowledge in communications which can be given by providing information, while some others need to be practiced in the classroom and also to be applied in the real communication practices. In learning and understanding cultural differences, we can focus on the empowerment of student centered learning, by asking students to explore these differences, select which should be practiced and applied, as well as decide which activities that should always be supervised by the teacher, so misunderstanding would not occur.